2018
DOI: 10.1002/ece3.4699
|View full text |Cite
|
Sign up to set email alerts
|

Context‐dependent costs and benefits of tuberculosis resistance traits in a wild mammalian host

Abstract: Disease acts as a powerful driver of evolution in natural host populations, yet individuals in a population often vary in their susceptibility to infection. Energetic trade‐offs between immune and reproductive investment lead to the evolution of distinct life history strategies, driven by the relative fitness costs and benefits of resisting infection. However, examples quantifying the cost of resistance outside of the laboratory are rare. Here, we observe two distinct forms of resistance to bovine tuberculosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 120 publications
(193 reference statements)
1
22
0
Order By: Relevance
“…Alternatively, there may be a role for differences in susceptibility between BTB and control animals. Previous work has suggested that susceptibility to BTB in buffalo may have a genetic basis, and while the mechanism for susceptibility is unknown, it is possible that the genetic background of the individuals that acquire BTB may affect other diseases as well (42). Finally, it is possible that there are parasite assemblages that protect against the invasion of BTB within an individual; however, our indicator species analysis revealed that none of the parasites that we examined were strongly associated with the BTB phase 1 group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, there may be a role for differences in susceptibility between BTB and control animals. Previous work has suggested that susceptibility to BTB in buffalo may have a genetic basis, and while the mechanism for susceptibility is unknown, it is possible that the genetic background of the individuals that acquire BTB may affect other diseases as well (42). Finally, it is possible that there are parasite assemblages that protect against the invasion of BTB within an individual; however, our indicator species analysis revealed that none of the parasites that we examined were strongly associated with the BTB phase 1 group.…”
Section: Discussionmentioning
confidence: 99%
“…We studied the effects of a well-characterized emerging, chronic parasitic disease, bovine tuberculosis (BTB) (17,(38)(39)(40)(41), on a community of 16 parasites in wild African buffalo (Syncerus caffer). We focus on BTB because is known to have dramatic effects on immune function (17,42,43) and body condition (i.e., wasting) (19,41,42); both are attributes that might permit the parasite to serve a "keystone" role, allowing us to evaluate how 1 parasite can restructure the rest of the parasite community. We developed a trait database for a diverse parasite community composed of viruses, bacteria, protozoa, and helminths and applied taxonomic-and trait-based approaches to analyze how parasite richness and community composition changed in response to BTB infection.…”
Section: Significancementioning
confidence: 99%
“…For our study, we inferred genetic relatedness among samples based on multilocus SNP genotypes and then used the genetic relatedness matrix derived from these SNPs to estimate genetic variance components. For this analysis, we used the “ related ” package in R and used the method described by Queller and Goodnight to calculate genetic distance between samples (Muir & Frasier, ; Queller & Goodnight, ; Tavalire et al, ). After developing this matrix of genetic relatedness among samples, we analysed variation in bleaching responses in the context of these relationships to estimate heritability.…”
Section: Methodsmentioning
confidence: 99%
“…After developing this matrix of genetic relatedness among samples, we analysed variation in bleaching responses in the context of these relationships to estimate heritability. Using the R package “ regress ,” we created a linear mixed model with symbiont clade type and population source as fixed effects (site where samples were collected; Tavalire et al, ). This analysis accounted for variation in thermal bleaching responses attributable to these specific factors.…”
Section: Methodsmentioning
confidence: 99%
“…The Lower Sabie (LS) and Crocodile Bridge (CB) herds, although genetically panmictic (Tavalire et al, ), utilize distinct areas within KNP with different underlying geological features, which give rise to different soils and associated vegetation (Venter et al, ). Water distribution (both natural and artificial) within the areas used by the herds also varies (Gaylard, Owen‐Smith, & Redfern, ).…”
Section: Methodsmentioning
confidence: 99%